Association of Adiponectin and Oxidized HDL with ABO Blood Groups in Fatty Liver Patients: Adiponectin and Oxidized High Density Lipoprotein in Fatty Liver - Nawaz, Naveeda; Arif, Saba; Anwar, Rehan; Riaz, Adnan; Ayyub, Asima; Javed, Rafia (Pakistan Journal of Health Sciences, 2024)
Non-Alcoholic Fatty Liver Disease (NAFLD) is a group of liver diseases that are not brought on by alcohol usage and are defined by an excessive buildup of fat in the liver cells. Objective: To identify the relationship between the Body Mass Index (BMI) and liver function markers in the study group, as well as Oxidized High-Density Lipoprotein (oxHDL) levels. Methods: This study was conducted at the University of Lahore, for the duration of six months from January 2022 to June 2022. For determining the role of adiponectin and oxHDL, (n=200) patients and divided into two group, healthy group (n=100) and disease group (n=100) participants. Biochemical identification, liver function test, lipid profile test and ELISA was done for analyzing the association with NAFLD. SPSS software was used for statistical analysis. Results: In this study different parameters were used that’s values of parameters mean of cases according to blood group system were varied than normal range, such as adiponectin level, BMI, oxLDL, oxHDL, ALT, AST, ALP, Cholesterol level, d-LDL, Calculated LDL, sdLDL, V-LDL, Triglyceride level, Apolipoprotein-B level was significantly higher and AST/ALT Ratio values, albumin, HDL were slightly less than normal values. O Blood groups was reported very low risk of fatty liver patients due to high adiponectin. Conclusions: From analysis it was concluded, that adiponectin and oxHDL associated with high risk of non-alcoholic fatty liver disorder.